Integrating the Sibelius App into Learning Traditional Dayak Music Rhythmic Patterns to Enhance Musical Creativity - Hendro T.G Samosir; Muhammad Ahsin Maulana; Mastri Dihita Sagala; Mastri Dihita Sagala (Universitas Negeri Medan, 2026)
This study examines the integration of Sibelius, a digital music notation software, as an innovative pedagogical medium in teaching Dayak traditional rhythm patterns to enhance students’ musical creativity. Traditional music instruction, which predominantly relies on oral and imitative approaches, often lacks systematic structure and limits students’ conceptual understanding and creative development. Addressing this gap, this research employs a descriptive qualitative design conducted at Sanggar Panatau Kameluh Bulan involving 26 students. Data were collected through observation, interviews, performance tests, and documentation of students’ musical works. The findings indicate that the use of Sibelius significantly improves students’ cognitive understanding of rhythmic structures through visual notation, enhances psychomotor skills in performing rhythm patterns, and increases affective engagement toward traditional music learning. Moreover, students demonstrate notable development in musical creativity, as reflected in their ability to explore, modify, and create new rhythmic variations based on traditional patterns. The study also reveals that digital notation serves as an effective bridge between oral tradition and modern pedagogical practices, supporting both learning innovation and cultural preservation. Despite challenges related to technological access and varying levels of digital literacy, the integration of Sibelius offers a relevant and adaptable model for technology-based music education. This research contributes to the development of culturally responsive and innovative music pedagogy in the digital era.